Lifetime improvement in silicon wafers using weak magnetic fields - Kuryliuk, A.; Steblenko, L.; Nadtochiy, A.; Korotchenkov, O. (Materials science in semiconductor processing, 2017)
We improve the lifetime of n-type Czochralski-grown silicon wafers using weak magnetic fields. This processing is found to increase carrier lifetimes by up to a factor of 2, from about 3μs to 7μs in our samples. Employing atomic and magnetic force microscopy, surface photovoltage transients, and X-ray photoelectron spectroscopy technique, we show that the effect can be explained by the magnetic field stimulated impurity diffusion from a bulk into the crystal surface, which forms impurity nanoclusters on the surface that can serve as centers of absorption of chemical elements from the environment. This, in turn, increases the oxide film thickness. We furthermore assume that the growth of SiO2 leads to negatively charged oxygen species in the vicinity of the Si/SiO2 interface. The existence of a local electric field generated by the charged areas can thus cause surface gettering by the positively charged metal ions, such as K+, Na+, Ca+, Al+, moved from the wafer bulk. Exposure to weak magnetic fields is therefore assumed to be important for the cost effective overall gettering efficiency during processing of silicon wafers for solar cell production.